2007
DOI: 10.2174/187436410701011014
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Signal Intensity of Magnetic Resonance Images in Optic Neuritis

Abstract: Abstract:We have evaluated the signal intensity of magnetic resonance (MR) images of the optic nerve quantitatively in 25 patients with unilateral acute optic neuritis (ON). MR imaging was performed with a 1.5 Tesla unit before treatment within 2 weeks after the onset of ON. Four coronal fat-suppressed T2-weighted images were obtained at 5, 10, 15, and 20 mm behind the eye. The ratio of the signal intensity of the MR images from the optic nerve to that of the white matter of the frontal lobe was calculated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Another study from Hanawa and Mizota. 24 found that the normal optic nerve shows the signal intensity of white matter. To our knowledge, the normal signal intensity of the oculomotor nerve on CE 3D FLAIR images has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Hanawa and Mizota. 24 found that the normal optic nerve shows the signal intensity of white matter. To our knowledge, the normal signal intensity of the oculomotor nerve on CE 3D FLAIR images has not been described.…”
Section: Discussionmentioning
confidence: 99%